2005
DOI: 10.1161/circulationaha.104.512475
|View full text |Cite
|
Sign up to set email alerts
|

Strut Position, Blood Flow, and Drug Deposition

Abstract: Background-The intricacies of stent design, local pharmacology, tissue biology, and rheology preclude an intuitive understanding of drug distribution and deposition from drug-eluting stents (DES). Methods and Results-A coupled computational fluid dynamics and mass transfer model was applied to predict drug deposition for single and overlapping DES. Drug deposition appeared not only beneath regions of arterial contact with the strut but surprisingly also beneath standing drug pools created by strut disruption o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
64
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(69 citation statements)
references
References 34 publications
4
64
0
1
Order By: Relevance
“…In fact, diffusion kinetics modeling of stent struts points toward serum diffusion as an important mechanism of drug delivery into the local endothelium. 37,38 In addition, oral administration of cell-cycle inhibitors prevent in-stent restenosis as well atherosclerotic progression in heart transplant patients, suggesting that serological delivery of drug, without high tunical concentrations, is able to affect stenotic progression. 9,29 Downstream endothelial effects should therefore be expected, in addition to effects on circulating macrophages and lymphocytes that are central to the development and progression of atherosclerotic plaques.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, diffusion kinetics modeling of stent struts points toward serum diffusion as an important mechanism of drug delivery into the local endothelium. 37,38 In addition, oral administration of cell-cycle inhibitors prevent in-stent restenosis as well atherosclerotic progression in heart transplant patients, suggesting that serological delivery of drug, without high tunical concentrations, is able to affect stenotic progression. 9,29 Downstream endothelial effects should therefore be expected, in addition to effects on circulating macrophages and lymphocytes that are central to the development and progression of atherosclerotic plaques.…”
Section: Discussionmentioning
confidence: 99%
“…13 A systemic concentration of 1.1 g/ml rapamycin was obtained after deployment of 2 SES and was associated with markedly delayed endothelization, enhanced platelet aggregation, and stent thrombosis. 14 The incidence of stent thrombosis in the modern era of stent deployment varies from a low of 0.5% to 1.9% with BMS implantation, the same as with DES implantation.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that release kinetics and applied drug dose modulate arterial drug deposition, distribution, and retention. In another study (Balakrishnan et al, 2005), drug deposition for single and overlapping DES was studied using coupled computational fluid dynamics and mass transfer reactions. It was proved that drug deposition occurs less via contact between the drug coating and the arterial wall than via flow-mediated deposition of blood-solubilized drug.…”
Section: Computational Modelingmentioning
confidence: 99%
“…Various limiting factors force them to apply a simplified approach. These models (Balakrishnan et al, 2005;Balakrishnan et al, 2007;Prabhu and Hossainy, 2006;Vergara and Zunino, 2007) utilized diffusion as a major driving force for drug release, while the other transport forceconvection is overlooked, which has a potential impact on transmural drug transport in tissues. Moreover coronary arteries are a dynamic environment with the presence of atherosclerotic calcified lesions, thrombus generating platelets, biological proteins, enzymes and other blood components which eventually influence the programmed drug eluting characteristics of any implant.…”
Section: Computational Modelingmentioning
confidence: 99%